CLONING OF ANTIGEN 85A ISOLATED FROM MYCOBACTERIUM TUBERCULOSIS INTO E.COLI DH5Α HOST - FARZAD EMAMI; SELVAM ARJUNAN; RADHAKRISHNAN SENTHILKUMAR (International Journal of Pharma and Bio Sciences, 2014)
Previous studies of antibody responses to Mycobacterium tuberculosis antigens at different stages of tuberculosis (TB) and in different classes of TB patients provided evidence that the profile of antigens recognized by antibodies is altered with disease progression. M. tuberculosis is a slow-growing organism, and it takes several weeks to months for an infection to progress to clinical TB. Approaching into the antigens expressed in vivo during subclinical TB could contribute to our understanding of the host pathogen interaction that leads to progression to clinical TB. Many amplification targets for M. tuberculosis have been reported. One of the more common PCR targets is the antigen 85A, specific for M. tuberculosis complex. The proteins of the antigen 85 complex are major secretion products of Mycobacterium tuberculosis and Mycobacterium bovis and have been studied by independent investigators for at least three decades. In the present study mycobacterium tuberculosis bacteria were isolated from patient with pulmonary tuberculosis and using specific primer designed using Primer 3 plus software for the Mycobacterial antigen 85A gene. The amplified gene was ligated with T vector (pTZ57R/T) and transformed into DH5α cells. The plasmid DNA obtained was then confirmed by restriction digestion and sequence analysis. The sequence was found to be 98% similar to that obtained in GenBank. Dendrogram was constructed using ClustalW software to get the similarity of the sequence with the existing sequence in the NCBI. Further research is required to express the gene to get the protein antigen for the production antibodies or effective vaccine for Mycobacterium tuberculosis.